BENTUK PIAWAIAN PENDIDIKAN KERJA SOSIAL YANG DITERAPKAN DALAM PROGRAM KERJA SOSIAL: RESPON PELAJAR-PELAJAR DI UNIVERSITI AWAM, MALAYSIA: FORMS OF SOCIAL WORK EDUCATION STANDARDS APPLIED TO SOCIAL WORK PROGRAMS: RESPONSES OF STUDENTS AT PUBLIC UNIVERSITIES, MALAYSIA - Asalal, Nurzaimah; Abd Wahab, Haris (SARJANA, 2019)
Social work education standards are a guideline for the provision of courses in social work programs at the Bachelors and Masters Degree levels. Council on Social Work Education (CSWE) is the body responsible for providing educational standards in social work programs in the United States since 1952. The application of social work education standards has made students who follow social work programs at universities competent in practice. Students should obtain knowledge and skills in social work after the completion of their Bachelors level program. In the Malaysian context, there is no social work education standard for social work programs offered. The Joint Working Group on Social Work Education (JBKPKS) established in 2000 undertook the task of designing social work courses. The need for social work education standards is necessary because the practice of social work requiress trained and competent practitioners to assist individuals, groups and communities. Thus, this study involving 279 students in the final year of study in social work programs at public universities completed a questionnaire to identify the forms of social work education standards that have been applied to courses taken by students. Generally, the research findings indicate that the courses the students took in their respective social work programs at the bachelor’s level have complied with the social work education standards.